If a and b are zeroes of the quadratic polynomial 2x2 + 3x - 6, then find the values of (i) a2+b2 (ii) a3+b3 (iii) a− b (iv) a2 /b+ b2/a (v) a2+2
Answers
Answered by
30
Step-by-step explanation:
hope it helps
.
.
.
.
.
.
.
plzzzz give thnx and Mark as brainlist
Attachments:
![](https://hi-static.z-dn.net/files/dee/2c0e202289558ec86f04bcd7bbc60c8e.jpg)
![](https://hi-static.z-dn.net/files/df1/778fb883393821454dc15c332afba96f.jpg)
![](https://hi-static.z-dn.net/files/d5c/7ba5accef95bbcd15be88a470a00ae84.jpg)
![](https://hi-static.z-dn.net/files/d95/bbf92438c72a85c9d568f486ca38305a.jpg)
Answered by
1
Answer:
Refer the given solution.
Given:
2x² + 3x - 6
To Find:
(i) α² + β²
(ii) α³+β³
(iii) α − β
(iv) α²/β + β²/α
Step-by-step explanation:
Quadratic equation is 2x² + 3x - 6
a = 2, b = 3, c = -6
sum of roots:
(α + β) = -b/a = -3/2
product of roots:
(αβ) = c/a == -6/2 = -3
(i) α² + β² = (α + β)² - 2αβ
⇒ (-3/2)² - 2(-3)
⇒ 9/4 + 6
⇒ (9+24)/4
⇒ 33/4
(ii) α³+β³ = (α + β)³ - 3αβ(α + β)
⇒ (-3/2)² - 3(-3)(-3/2)
⇒ 9/4 - 27/2
⇒(9 - 54)/4
⇒ -45/4
(iii) α − β = √ (α + β)² - 4αβ
⇒ √(-3/2)² - 4(-3)
⇒ √(9/4 + 12)
⇒ √(9 + 48)/4
⇒ √ (57/4)
⇒ (√57)/2
(iv) α²/β + β²/α = ( α³+β³)/αβ
⇒(-45/4)/-3
⇒ 45/12
⇒ 15/4
#SPJ2
Similar questions